A new methodology for measuring distortions to agricultural incentives for value chain analysis - Tokgoz, Simla; Majeed, Fahd (2017)
We propose a new methodology to measure distortions to agricultural incentives for economic agents along the value chains and for the complete value chains of agricultural commodities. We use an amalgamated value chain approach, including the primary producers and the processors of commodities. We apply this methodology to selected value chains in the Indian agricultural market: rapeseed complex, groundnut complex, ethanol-molasses-sugar-sugarcane.